PENGARUH PENDELEGASIAN DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS PEGAWAI STIKES BINA PUTERA BANJAR, JAWA BARAT - Nelma Ariestien Sahureka (Jurnal Manajemen Pendidikan, 2015)
The objective of this research is to understand comprehensively the effect of delegation and job satisfaction toward productivity of the employee in the STIkes Bina Putera Banjar, West Java. The research used a survey method with path analysis applied in testing hyphotesis. It was conducted to 105 employees as the respondents which were selected in a simple random way. The data analysis and interpretation reveals that (1) delegation has direct positive influence toward productivity, (2) job satisfaction has direct positive influence toward productivity, (3) delegation has direct positive influence toward job satisfaction.